The Pentecostal gender paradox: eschatology and the search for equality - Dutko, Joseph Lee (T&T Clark systematic Pentecostal and charistmatic theology, 2023)
"The purpose of this project is to critically assess the relationship between gender and eschatology in the early Pentecostal movement, key biblical texts, theology, and praxis, in order to develop a thoroughly eschatological basis for the full flourishing and unrestricted inclusion of women in all parts and at all levels of church life, ministry, and society"--